THE OBLIGATION TO USE A HOLDER FOR ONLINE MOTORCYCLE TICKET RIDERS FROM THE PERSPECTIVE OF SADD ADZ DZARI'AH AND LAW NUMBER 22 OF 2009 CONCERNING TRAFFIC AND ROAD TRANSPORTATION - Liza Arlina; Uswatun Hasanah (Program Pascasarjana UIN Sumatera Utara, 2025)
The use of mobile phones without holders while driving has become a common habit among online motorcycle taxi drivers. This practice is driven by job demands that require drivers to stay connected to the ride-hailing app, navigation, and customers. However, using a phone without a holder can disrupt concentration, increasing the risk of accidents and endangering both the rider and other road users. The absence of explicit regulations mandating the use of phone holders creates a regulatory gap with potentially harmful consequences. This study aims to analyze the safety risks and impacts of using phones without holders while driving, as well as examine the urgency of enforcing holder usage obligations from the perspective of Sadd adz-Dzari'ah (Blocking the Means to Harm) and its relevance to Law No. 22 of 2009 concerning Road Traffic and Transportation. The research employs an empirical juridical approach with case study and sociological methods, collecting data through literature reviews and interviews.The findings indicate that using a phone without a holder while driving increases the risk of accidents for online motorcycle taxi drivers due to impaired concentration and vehicle control. From the perspective of Sadd adz-Dzari'ah, although using a phone without a holder is initially permissible (mubah), it leads to harm (mafsadat) and must therefore be prevented. Juridically, this practice also violates Article 106 Paragraph (1) of the Road Traffic and Transportation Law. Hence, the use of phone holders should be mandated as part of road safety standards.